Konsep Diri Virtual dalam Komunikasi Hiperpersonal Pengguna Dating App Tinder untuk Mencari Pasangan di Yogyakarta - Kiksen, Yosef Aryanto Wicaksono; Nurdiarti, Rosalia Prismarini (Yayasan Lentera Avanya Nagari, 2023)
Tinder is one of the most popular dating applications in Indonesia which is often used to find a partner because of the large number of users. However, there are several other motives for using Tinder by its users. This study aims to determine how the virtual self-concept is formed by users of the Tinder Application in finding a partner. The type of research carried out by the researcher is qualitative with interviews and observations in previous studies. This study was analyzed using the self-concept theory by William H. Fitts to examine the dimensions of the virtual self-concept by Tinder users. The results of the research obtained are that the virtual self-concept presented by male and female users is that they feel they do not want to overestimating themselves, but also not too low as self-esteem. Second, users provide a self-concept that seems friendly and open in order to get to know each other more closely with other people.